Differential prognostic impact of myelodysplasia-related gene mutations in a European cohort of 4978 intensively treated AML patients - Bill, Marius; Sauer, Tim; Heuser, Michael; Müller-Tidow, Carsten (Leukemia, 2025)
In the European LeukemiaNet (ELN) 2022 recommendations, myelodysplasia-related (MR) gene mutations were classified as a novel adverse prognostic category for intensively treated acute myeloid leukemia (AML). To assess the prognostic impact of individual MR genes within the ELN, clinical, cytogenetic, and molecular data from 4,978 intensively treated AML patients were analyzed. Remission rates and survival outcomes were evaluated. For analyses in context of ELN2022 classification, patients carrying an MR mutation were excluded from the adverse group and analyzed separately; those with co-occurring favorable or intermediate features remained in their respective groups. Overall, 1698 patients (34.1%) harbored at least one MR mutation. Lower complete remission rates were observed in MR-mutated cases (65.7% vs 77.7%; p < 0.001) along with shorter event-free (HR 1.45; p < 0.001), relapse-free (HR 1.33; p < 0.001), and overall survival (HR 1.45; p < 0.001) were recorded. Gene-specific prognostic patterns emerged: ASXL1, RUNX1, SF3B1, and U2AF1 mutations associated with adverse risk-like outcomes; SRSF2 and STAG2 aligned with intermediate-risk; BCOR, EZH2, and ZRSR2 did not differ significantly from intermediate or adverse risk. These findings from a large cooperative cohort highlight prognostic heterogeneity among MR mutations and suggest that SRSF2 and STAG2 mutations are associated with less adverse risk patterns, comparable to intermediate-risk.